Hubungan Koordinasi Mata dan Kaki Terhadap Kemampuan Dasar Passing Futsal - Tommy Soterio Maitimu, Gilbert; Pratama, Leo; Aji Suryo Putro, Waskito (Jurnal Muara Olahraga, 2024)
The aim of this research is to find out whether there is a relationship between eye and foot coordination on the basic passing techniques in the game of futsal. The method used is quantitative research with eye and foot coordination tests and also the Small-Side Games passing test which takes place at the UNIMUDA Sorong Basketball Court. with 10 players as the subject, the data collection technique used was observation, then the data obtained was analyzed from the eye and foot coordination normality test data and obtained a significant value = 0.245 (sig. > 0.05), so this result shows the eye and foot coordination test data The feet are normally distributed.The basic passing technique obtained a significant value = 0.466 (sig > 0.05), so this result shows that the basic passing technique test data is normally distributed. The results of data analysis of eye and foot coordination on passing ability obtained an R value of 0.671 (P>0.05). With a degree of determination of 0.450 or providing a contribution of 45.0%. Which means there is a significant contribution/relationship between eye and foot coordination on basic futsal passing abilities.